2000
DOI: 10.1046/j.1365-2958.2000.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of in vivo attenuated mutants of Brucella melitensis

Abstract: SummaryBrucella melitensis 16M is a Gram-negative a 2 -proteobacterium responsible for abortion in goats and for Malta fever in humans. This facultative intracellular pathogen invades into and survives within both professional and non-professional phagocytes. Signature-tagged mutagenesis (STM) was used to identify genes required for the in vivo pathogenesis of Brucella. A library of transposon mutants was screened in a murine infection model. Out of 672 mutants screened, 20 were not recovered after a 5 day pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
123
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 56 publications
4
123
3
1
Order By: Relevance
“…inside the macrophage is a prerequisite to the understanding of the relation with the macrophage. Signature-tagged mutagenesis and differential fluorescence induction approaches were recently used to identify genes required for virulence in a murine model of infection and in human and murine macrophages (5)(6)(7)(8)(9). A large proportion of these genes encode enzymes of various metabolic pathways.…”
mentioning
confidence: 99%
“…inside the macrophage is a prerequisite to the understanding of the relation with the macrophage. Signature-tagged mutagenesis and differential fluorescence induction approaches were recently used to identify genes required for virulence in a murine model of infection and in human and murine macrophages (5)(6)(7)(8)(9). A large proportion of these genes encode enzymes of various metabolic pathways.…”
mentioning
confidence: 99%
“…Notably, we found that the ORF BMEI1759 possesses a missense mutation (c.523G> C) in the Rev.1 genome. This ORF encodes the vitamin B12-dependent methyltransferase MetH, which is involved in methionine biosynthesis and was previously screened in a murine infection model aimed at identifying pathogenic Brucella genes expressed in vivo [28,42]. Thus, we suggest that mutations in Rev.1 genes that encode enzymes involved in amino acid biosynthesis may contribute to the attenuation of this strain.…”
Section: Resultsmentioning
confidence: 99%
“…We described previously (Lestrate et al, 2000) that the G4 mutant bearing a miniTn5 inserted between prlS and prlR is attenuated in mice. Therefore, we started to characterize this TCS and its putative function further.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these systems have been characterized previously in some Brucella species: BvrSR (Sola-Landa et al, 1998), FeuQP (Dorrell et al, 1998), NtrBC (Dorrell et al, 1999), NtrXY (Carrica et al, 2012;Foulongne et al, 2000), the flagellar master regulator FtcR (Léonard et al, 2007), the CtrA phosphorelay (Hallez et al, 2007), the blue-light-activated LOV HKs (Swartz et al, 2007) and CenR (Zhang et al, 2009). Some other TCSs have been identified by transpositional mutagenesis during global screening for virulence factors (Lestrate et al, 2000;Wu et al, 2006) but left uncharacterized. This is the case for the Brucella melitensis transpositional mutant (G4) that we identified in a previous study (Lestrate et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation